Pediatric thyroid nodules: A single center experience. (August 2016) - Trahan, Jason; Reddy, Abhita; Chang, Ellen; Gomez, Ricardo; Prasad, Pinki; Jeyakumar, Anita
Abstract: Objectives: 1. Analyze our center's experience with thyroid nodules. 2. Evaluate the efficacy of fine needle biopsy. 3. Compare our experience with the 2015 ATA guidelines. Methods: IRB approved retrospective chart review from July 1993–July 2014 at a tertiary pediatric institution. Patients under age 21 with documented thyroid nodules who underwent fine needle aspiration, and/or thyroidectomy were included. Results: 126 patients were identified. 84.1% (n = 106) were female. Age range was 12 months–20 years. The average age was 13.3 ± 4.1 years. The nodules ranged from 0.5 cm to 6 cm 53.9% (n = 68) had a fine needle biopsy done. 42.6% (n = 29) fine needle biopsies were benign, 26.5% (n = 18) were non-diagnostic, 13.2% (n = 9) were classified as "atypia", 0.09% (n = 6) were consistent with thyroiditis, and 0.09% (n = 6) were suspicious for papillary carcinoma. 78.6% (n = 99) underwent surgery. 7 patients with "benign" needle biopsies underwent surgery: all had follicular adenoma. 7 patients with "atypia" needle biopsies underwent surgery: one patient had papillary thyroid cancer. 8 patients with non-diagnostic needle biopsies underwent surgery: one patient had papillary thyroid cancer. All the patients with needle biopsy suspicious for papillary carcinoma had papillary carcinoma on final pathology. 99 patients underwent surgery: 14.1% (n = 14) had papillary carcinoma and 2% (n = 2) had medullary carcinoma. Conclusion: Our review of pediatric thyroid nodules at our institution supports data previously reported. 84% of identified patients were female, supporting previous data that nodules are more prevalent in the female population. Of the 126 patients identified, 12.7% had thyroid carcinoma, supporting the 7–25% range described in previous literature. Our institution showed a high positive predictive value of FNA for papillary thyroid carcinoma.